Long Odds - Haggard, H. Rider (Henry Rider), 1856-1925 (Salt Lake City, UT : Project Gutenberg, 2006)
"Long Odds" by H. Rider Haggard is a thrilling adventure novel written during the late 19th century (Victorian era). The book follows Allan Quatermain, a seasoned hunter, as he recounts a harrowing tale of survival and peril during his expeditions in Africa. The story intertwines themes of exploration, danger, and the raw power of nature, highlighting Quatermain's encounters with lions and the harsh realities of life in the wild. In this gripping narrative, Quatermain shares a series of events that unfold during one of his hunting trips, where he navigates through the fever-stricken wilderness of Sikukuni's country. The tale recounts his encounters with deadly wildlife, particularly a pride of lions that lead to a fateful confrontation. After a series of precarious situations and attempts at bravery, Quatermain ultimately faces the lions directly, culminating in an intense battle that leaves him wounded. As he reflects on the odds stacked against him, he realizes the folly of taking on such formidable adversaries alone. The story captures both the excitement of adventure and the sobering consequences of underestimating nature's dangers. (This is an automatically generated summary.)
Release date is 2006-03-31
Produced by John Bickers; Dagny; Emma Dudding; David Widger
Keywords: Africa -- Fiction; Adventure stories; Hunting guides -- Fiction; Quatermain, Allan (Fictitious character) -- Fiction